2007
DOI: 10.1007/bf03168224
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de reserpina y p-cloranfetamina en el metabolismo y la liberación de 5-HT en el ganglio cerebral de Inachis io (Lepidoptera).

Abstract: There have been few pharmacological studies of serotonergic system dynamics in insects. A more precise knowledge of the response of serotonergic neurons to drugs will contribute to understanding of the role of this neurotransmitter in insect behaviour. The present work was carried out to study several aspects of serotonin (5-HT) metabolism and release in an insect, the butterfly Inachis io. The effects of a single intra-abdominal injection of reserpine (30 pg/insect) or p-chloroamphetamine (50 microg/insect) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Reserpine selectively depleted octopamine, dopamine and serotonin in the nervous system of the cockroach, Periplaneta americana (Sloley and Owen, 1982; Sloley and Orikasa, 1988). The amine-depleting effect of reserpine has also been demonstrated in beetles, blow flies, honeybees, crickets, and butterflies (Masner et al, 1970; Brookhart et al, 1987; Menzel et al, 1999; Stevenson et al, 2000; Vieira et al, 2007). Reserpine was reported to act as a chemosterilant when fed to the Mediterranean fruit fly, Ceratitis capitata , where fertility and fecundity were interrupted (Cohen, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…Reserpine selectively depleted octopamine, dopamine and serotonin in the nervous system of the cockroach, Periplaneta americana (Sloley and Owen, 1982; Sloley and Orikasa, 1988). The amine-depleting effect of reserpine has also been demonstrated in beetles, blow flies, honeybees, crickets, and butterflies (Masner et al, 1970; Brookhart et al, 1987; Menzel et al, 1999; Stevenson et al, 2000; Vieira et al, 2007). Reserpine was reported to act as a chemosterilant when fed to the Mediterranean fruit fly, Ceratitis capitata , where fertility and fecundity were interrupted (Cohen, 1983).…”
Section: Introductionmentioning
confidence: 95%
“…Result of a study showed that reserpine effect on the metabolism of serotonin in the brain ganglia of Inachisio [Lepidoptera] [7]. Demand of reserpine in Indonesia is increasing, but the supply of materials of this compound depending on availability of the plant growing in nature because this plant is rarely cultivated that the plant is now rarely found in nature [8]. Therefore, it is a need to cultivate the plant in order to produce up to commercial scale to meet the market demand.…”
Section: Introductionmentioning
confidence: 99%
“…Substitutions to the amphetamine molecule give rise to a group of derivatives, and, as a result, a number of illegal, amphetamine‐like drugs are produced in underground labs for sale on the street . From the point of view of screening and the confirmation of amphetamine derivatives on the illicit market, more detailed detection and separation information would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%